PENGARUH ENTERPRISE RISK MANAGEMENT DAN PENGUNGKAPAN ESG TERHADAP NILAI PERUSAHAAN - Agnes Dea Natalia; Agus Purwanto (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of Enterprise Risk Management (ERM) and Environmental, Social, and Governance (ESG) disclosure on firm value. The dependent variable in this research is firm value, which is proxied by Tobin’s Q ratio, while the independent variables consist of ERM and ESG disclosure, including environmental, social, and governance aspects. ERM is measured using a dummy variable based on the fulfillment of at least four out of seven implementation criteria, while ESG disclosure data are obtained from ESG disclosure scores available in the Bloomberg database. The study uses secondary data derived from annual reports, sustainability reports, financial statements, and the Bloomberg database of 119 companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. Data analysis was conducted through classical assumption tests and multiple linear regression using Microsoft Excel and SPSS 26.The results indicate that social disclosure has a significant effect on firm value, while ERM, environmental disclosure, and governance disclosure do not show significant effects. Furthermore, the analysis results do not provide sufficient evidence that the influence of ERM and ESG on firm value is stronger in sensitive industries compared to non-sensitive industries. These findings suggest that social disclosure is an aspect of ESG that attracts greater attention from investors, while the implementation of ERM and the disclosure of environmental and governance aspects still need to be improved to create a more tangible impact on firm value.